Diet-derived circulating antioxidants and risk of epilepsy: A study combining metabolomics and mendelian randomization - Zhen Liang; Yingyue Lou; Zhaoshi Zheng; Qi Guo; Songyan Liu (Heliyon, 2024)
Background: Previous studies offer inconclusive results on the association between diet-derived circulating antioxidants and epilepsy. Objective: This study aims to assess oxidative stress presence in epilepsy patients' circulation and investigate the causal link between diet-derived circulating antioxidants and epilepsy. Methods: Untargeted metabolomics analysis was conducted on plasma samples from 62 epileptic patients and 20 healthy individuals to evaluate oxidative stress based on metabolite alterations in epilepsy patients' circulation. Two-sample Mendelian Randomization (MR) analysis examined the causation between diet-derived circulating antioxidants (measured by absolute levels and relative metabolite concentrations) and epilepsy, utilizing the inverse-variance weighted (IVW) method as the primary outcome, with complementary MR analysis methods (MR Egger, weighted median, weighted mode, and simple mode). Results: Untargeted metabolomics analysis revealed elevated circulating oxidizing metabolites (palmitic acid, oleic acid, linoleic acid, and myristic acid) and reduced reducing metabolites (glutamine) in epilepsy patients, providing robust evidence of oxidative stress. The IVW analysis indicated significantly reduced epilepsy risk (odds ratio: 0.552; 95% confidence interval: 0.335–0.905, P = 0.018) with genetically determined higher absolute circulating β-carotene. However, other diet-derived circulating antioxidants (lycopene, retinol, ascorbic acid, and selenium) and antioxidant metabolites (α-tocopherol, γ-tocopherol, ascorbic acid, and retinol) did not significantly associate with epilepsy risk. Additional MR analysis methods and heterogeneity assessments confirmed the results' robustness. Conclusion: This study provides compelling evidence of oxidative stress in epilepsy patients' circulation. However, the majority of diet-derived circulating antioxidants (lycopene, retinol, ascorbic acid, vitamin E, and selenium) are unlikely to causally associate with reduced epilepsy risk, except for β-carotene.